2012
DOI: 10.1159/000337528
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Survey of Chronic Intestinal Pseudo-Obstruction and Evaluation of the Newly Proposed Diagnostic Criteria

Abstract: Background and Aims: Chronic intestinal pseudo-obstruction (CIPO) is an intractable disease in which clinical symptoms of intestinal obstruction appear without mechanical cause. No clear diagnostic criteria have been established; therefore, we proposed diagnostic criteria to facilitate the diagnosis of this rare disease and aim to evaluate their usefulness and validity. Materials andMethods: A questionnaire was sent to 378 institutions belonging to the Japanese Society of Gastroenterology between December 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 18 publications
3
47
2
Order By: Relevance
“…Mid‐point 2014 census population data for the North East of England, as specified by the Office for National Statistics, UK (2,618,710),22 were used to estimate the prevalence rate of IPO in m.3243A>G‐related mitochondrial disease, as described previously 2. The minimum prevalence rate of IPO in clinically manifesting m.3243A>G carriers was estimated as 1 in 200,000 or 0.53 per 100,000 (95% confidence interval [CI]: 0.3–0.9 per 100,000), which is comparable to the previously published point prevalence of all‐cause chronic IPO (0.9 per 100,000) 23, 24. Furthermore, review of our patient cohort and the literature would suggest that this late gastrointestinal complication may occur in other primary mtDNA25, 26, 27, 28, 29 and nuclear mutations (up to 3% in POLG ‐related mitochondrial disease30, but is extremely rare.…”
Section: Discussionsupporting
confidence: 81%
“…Mid‐point 2014 census population data for the North East of England, as specified by the Office for National Statistics, UK (2,618,710),22 were used to estimate the prevalence rate of IPO in m.3243A>G‐related mitochondrial disease, as described previously 2. The minimum prevalence rate of IPO in clinically manifesting m.3243A>G carriers was estimated as 1 in 200,000 or 0.53 per 100,000 (95% confidence interval [CI]: 0.3–0.9 per 100,000), which is comparable to the previously published point prevalence of all‐cause chronic IPO (0.9 per 100,000) 23, 24. Furthermore, review of our patient cohort and the literature would suggest that this late gastrointestinal complication may occur in other primary mtDNA25, 26, 27, 28, 29 and nuclear mutations (up to 3% in POLG ‐related mitochondrial disease30, but is extremely rare.…”
Section: Discussionsupporting
confidence: 81%
“…This is probably due to enrollment of patients with colonic involvement, which appear at an older age. 10,11 The frequency with which the main symptoms appeared is similar to that observed in other studies; however, in our study, as in others, their intensity was not recorded. Thus, one might speculate that since pain is a very common symptom, its intensity may have been less than that described in the literature, since painkillers are not listed among the drugs received by the patients.…”
Section: Discussionsupporting
confidence: 92%
“…As in other studies with a similar number of patients, a predominance of females was observed, and most of the cases corresponded to primary CIPO. 4,10,12,13 The average age of our patients at diagnosis was similar to that described in European studies 12 and significantly younger than the age observed in Japanese studies. This is probably due to enrollment of patients with colonic involvement, which appear at an older age.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Eligible CIPO patients were identified via specialist gastrointestinal clinics. To be eligible, patients had to meet the diagnostic criteria for CIPO proposed by the Japanese Ministry of Health, Labour, and Welfare, 14 including documented pathological bowel dilatation in the absence of mechanical obstruction on imaging. The patients underwent FMT between December 2014 and September 2015.…”
Section: Patientsmentioning
confidence: 99%